Isolation and amplification of 16S rRNA gen of Associated Microbial isolates in Red Algae Kappaphycus alvarezii from Belang, Southeast Minahasa Regency, North Sulawesi - Letha L. Wantania; Stenly Wullur; Elvi L. Ginting; Desy M. H. Mantiri; Suzanne L. Undap; Deiske A. Sumilat; Grevo S. Gerung (Jurnal Ilmiah PLATAX, 2019)
This study aims to obtain isolates and amplify the associative bacterial 16SrRNA gene in K. alvarezii algae. The K. alvarezii algae was collected from seaweed cultivation area in Belang, Southeast Minahasa, North Sulawesi. Associative bacteria were sampled from K. alvarezii algae, grown in Nutrient Agar and separated based on their morphological characteristics. Each isolates were extracted their DNA genome and.the16S rRNA gene of each isolate was amplified using PCR. Eight associative bacterial from K. alvarezii algae were successfully isolated based on morphological characteristics which were dominated by round shape, smooth edges, convex elevation, and white color of the isolates. The results of genomic DNA extraction from each of these isolates were successfully used as templates to amplify the 16s rRNA gene.Key word: Bacteria, Kappaphycus alvarezii, Taxsonomy, 16S rRNAABSTRAKPenelitian ini bertujuan untuk mendapatkan isolat dan mengamplifikasi gen 16SrRNA bakteri asosiatif pada alga K. alvarezii. Metode penelitian diawali dengan pengambilan sampel alga K. alvarezii di lokasi pembudidayaan rumput laut di desa Belang, Minahasa Tenggara, Sulawesi Utara. Selanjutnya, bakteri asosiatif pada alga K. alvarezii tersebut ditumbuhkan dalam media Nutrient Agar, isolat yang tumbuh kemudian dipisahkan berdasarkan karakteristik morfologinya. dan gen 16S rRNA masing-masing isolat diamplifikasi menggunakn PCR. Delapan isolat bakteri asosiatif pada alga K. alvarezii berhasil diisolasi dengan karakteristik morfologi berbeda yang didominasi dengan bentuk round, tepian smooth, elevasi convex, dan warna putih. Hasil ekstraksi DNA genom dari masing-masing isolat tersebut berhasil digunakan sebagai template untuk mengamplifikasi gen 16s rRNA.Kata Kunci: Bakteri, Kappaphycus alvarezii, Taksonomi, 16S rRNA